The Influence of Scientific Approach on the Result of Learning Natural Science in Class V SD Negeri 1 Segalamider at Bandar Lampung - Nureva, Nureva; Melinda, Mella (CV. Creative Tugu Pena, 2021)
The main problem in this study is the low learning outcomes of Natural Science obtained by Class V SD Negeri 1 Segalamider Bandar Lampung for the 2019/2020 academic year. This study aims to determine the effect of the Scientific Approach on students' learning outcomes of natural science. This research uses influence study research method. This research was conducted at SD Negeri 1 Segalamider with a sample size of 27 students. The analysis used is the Hypothesis Test using the Dependent Sample T-test, namely Paired Sample T-test (Paired Sample T-Test). The results of this study indicate that the hypothesis testing results obtained by tcount> ttable, namely tcount of 7,834 with ttable of 2,056. With a significant level of 0.05 or 5%, which means that Ha is accepted and H0 is rejected. This means that the scientific approach has an effect on the learning outcomes of class V SD Negeri 1 Segalamider Bandar Lampung for the 2019/2020 academic year. Keywords: Scientific Approach, Science Learning Outcomes, Learning Natural Science